Ambiguity in XiTsonga - Hlongwana, Colfar (University of Limpopo, 2015)
The aim of this study is to investigate ambiguity in Xitsonga. There are many kinds of ambiguity, but the study mainly focuses on lexical and structural ambiguity. Lexical ambiguity occurs at word level and is caused by homonyms (homophones and homographs) and polysemes. Structural ambiguity occurs at sentence level. This kind of ambiguity manifests in the structure of the sentence itself. Data were collected through self-observation as a native Xitsonga speaker. Words and sentences with multiple meanings in Xitsonga were listed and tree diagrams were used to illustrate and disambiguate ambiguity. The study reveals that, like other languages, Xitsonga has words and sentences with double or many meanings. KEYWORDS AMBIGUITY, LEXICAL AMBIGUITY, STRUCTURAL AMBIGUITY, HOMONYM, HOMOPHONES, HOMOGRAPHS, POLYSEMES.
Thesis (M.A. (Translation studies and Lingustics)) --University of Limpopo, 2015
Keywords: Lexical ambiguity; Language structural ambiguity; Tsonga homonyms; Tsonga homophones; Tsonga polysemes; Tsonga homographs; Ambiguity in literature; Tsonga Language -- Dialect -- Lexicology